Etude De La Diversite Des Termites (Isoptera) Dans Quelques Localites De La Region De Kolda (Haute Casamance, Senegal) - Sane, Hassoum; Samb, Tamsire; Ndiaye, Abdoulaye Baïla; Tidiane Ba, Cheikh (European Scientific Journal, ESJ, 2016)
Termites (Isoptera) are invertebrates that play many ecological functions in terrestrial ecosystems, especially in tropical areas. Their impacts on the quality and the fertility of the soil are well known. However, in Senegal termite fauna is still poorly known. Thus, to contribute to the knowledge of termites of Senegal we have conducted a study on their diversity in the region of Kolda (Casamance). Termites were sampled in transects of 100 m long and 20 m wide. Termite workers, soldiers and some time reproductives are collected in vials filled with ethanol 70°. Thirty (30) termite species have been identified. Five of them are new records for Senegal. The four trophic groups xylophagous, fungus-growing termites, harvester or foraging termites and soil-feeding were represented. The fungusgrowing termites are more diversified. According to the types of nests, termites encountered are divided into 3 groups. The more diversified are those that build ground-nest without fungus.